2021
DOI: 10.5772/intechopen.99169
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E in Human Health and Oxidative Stress Related Diseases

Abstract: Oxidative stress characterized by an imbalance in the production and degradation of radical species has been implicated in the onset and progression of several diseases. The efficacy of antioxidants acting via the inhibition of radical chain reactions, scavenging of free radicals, direct donation of electrons to radical species and chelation of metal ions have been reported to attenuate the oxidative process. Vitamin E is an effective antioxidant and its hydrophobic nature and membrane permeability offer some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…However, the applications of vitamin E are limited by its poor water solubility and susceptibility to degradation caused by environmental factors such as light, oxygen, and high pH. [9][10][11] Several techniques have been developed to recover vitamin E from palm oil. These include solvent extraction, [12][13][14] enzymatic process, [15][16][17] chemical modification through esterification 18 and molecular distillation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the applications of vitamin E are limited by its poor water solubility and susceptibility to degradation caused by environmental factors such as light, oxygen, and high pH. [9][10][11] Several techniques have been developed to recover vitamin E from palm oil. These include solvent extraction, [12][13][14] enzymatic process, [15][16][17] chemical modification through esterification 18 and molecular distillation.…”
Section: Introductionmentioning
confidence: 99%
“…All naturally occurring vitamin E forms are strong antioxidants with anti-inflammatory activities [33]. A recent review describes the capability of vitamin E to behave as an antioxidant and its effects on diseases caused by oxidative stress [34]. However, despite many studies that have reported on vitamin E's relationship with the immune system, the mechanistic details are lacking [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…It acts as the first line of defense against lipid peroxidation, protecting the cell membranes from free radical attack. 6 Vitamin E also possesses anti-cancer properties. This is probably because of its ability to stimulate the p53 tumor suppressor gene; the downregulation of mutant p53 proteins and his anti-angiogenic effect mediated by the blockage of transforming growth factor alpha.…”
Section: Introductionmentioning
confidence: 99%